Representasi Amerika Serikat dalam Wacana Perang Dagang AS-Tiongkok: Pendekatan Linguistik Fungsional Sistemik (SFL) - Mubarok, Yasir; Nurhuda, Zamzam (GERAM, 2025)
This study investigates how the United States is represented in discourses surrounding the US–China trade war. This study analyzes three political statement discourses related to US–China trade relations, namely statements from White House Press Secretary Karoline Leavitt, President Donald Trump, and Vice President JD Vance, obtained from official media sources and YouTube recordings in April 2025. This study uses a qualitative approach based on the Systemic Functional Linguistics (SFL) framework, focusing on the ideational metafunction transitivity system. The analysis was carried out using the Miles and Huberman (1994) approach, which includes data reduction, data presentation, and drawing and verifying conclusions. The results of the study found a total of 67 clauses obtained including material processes (46.27%), relational (32.84%) mental (13.43%), verbal (5.97%), and existential processes (1.49%). While the behavioral process (0%) was not found. Of the five processes found, the dominant material process (46.27%). This indicates that the US is an active actor in taking action. This study reveals how transitivity patterns shape conceptions of international relations and economic power. Through transitivity analysis, it has revealed how grammatical choices function to construct geopolitical narratives, the United States in the global realm.